Understanding the decision to marry versus cohabit: the role of interpersonal dedication and constraints and the impact on life satisfaction - Johnson, Matthew D.; Anderson, Jared R.; Aducci, C. J. (My University, 2013)
The current study explored men's and women's reasons for choosing to marry rather than to cohabit using a national data set (n = 786) of adults who were currently married or had been married previously. Using commitment theory participant's open-ended reasons for choosing to marry were coded into categories of either interpersonal dedication or constraint commitment. A variety of demographic, attitudinal, and relationship history variables were then used to predict commitment type. The influence of commitment type during the decision to marry on life satisfaction was also explored. Results indicate that current marital status (being married vs. being divorced or separated) and cohabiting before marriage were the strongest predictors of interpersonal dedication reasons for marriage for both men and women. Level of conventionality and parents' marital status also emerged as significant predictors of constraint commitment. Finally, marrying for reasons related to interpersonal dedication significantly predicted higher life satisfaction for men but not for women.
Keywords: Constraints; Interpersonal dedication; Life satisfaction; Marriage; Cohabitation